2016
DOI: 10.1002/cam4.734
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of health‐related quality of life for death risk stratification in patients with unresectable glioblastoma

Abstract: Glioblastoma is the most common malignant brain tumor in adults. Baseline health‐related quality of life (HRQoL) is a major subject of concern for these patients. We aimed to assess the independent prognostic value of HRQoL in unresectable glioblastoma (UGB) patients for death risk stratification. One hundred and thirty‐four patients with UGB were enrolled from the TEMAVIR trial. HRQoL was evaluated at baseline using the EORTC QLQ‐C30 and BN20 brain cancer module. Clinical and HRQoL parameters were evaluated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…There is no doubt that the increased incidence of GBM and the improvement in the treatment outcome will result in a higher prevalence of survivors, 12 but the HRQOL and functional outcome of these patients has so far been the subject of only a few studies. 4,5,7,13,15,16,19,20 Paquette et al 19 identified future uncertainty in unresectable GBMs as an independent predictor factor for OS, which was in line with financial worries. The ability to provide for one's economic self-sustenance not only impacts a person's socioeconomic quality of life but also affects the sense of future certainty and influences his or her self-worth and can be considered as a parameter of social reintegration.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…There is no doubt that the increased incidence of GBM and the improvement in the treatment outcome will result in a higher prevalence of survivors, 12 but the HRQOL and functional outcome of these patients has so far been the subject of only a few studies. 4,5,7,13,15,16,19,20 Paquette et al 19 identified future uncertainty in unresectable GBMs as an independent predictor factor for OS, which was in line with financial worries. The ability to provide for one's economic self-sustenance not only impacts a person's socioeconomic quality of life but also affects the sense of future certainty and influences his or her self-worth and can be considered as a parameter of social reintegration.…”
Section: Discussionmentioning
confidence: 90%
“…to the working capacity and not only allows individuals to maintain their social status but also affects the sense of future certainty, 19 which has been shown to represent an additional prognostic value for death risk stratification in unresectable GBM. 19 Numerous factors come into play in the socio-economic analysis of GBM patients, and the parameters to consider are multifactorial.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In self-assessments, however, a high nonresponse rate could be specific for glioma [ 14 ] since various physical and neuropsychological symptoms can complicate the use of screening instruments [ 15 ]. It is possible that the true rates of distress, mental and cognitive problems are higher than reported [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite multidisciplinary treatment approaches, including surgical resection and radiotherapy, GBM has a low prognosis with an average survival period of 15 -18 months (124)(125)(126). A major challenge in the treatment of GBM is delivering the therapeutic drug across the blood-brain barrier (BBB), a network of specialized brain endothelial cells with intercapillary distances of ~40µm that tightly regulate ionic composition, prevent macromolecules and unwanted cells from entering the brain to protect the central nervous system (CNS) from neurotoxins (127)(128)(129)(130)(131).…”
Section: Introductionmentioning
confidence: 99%